Medical student learner neglect in the clinical learning environment: Applying Glaser's theoretical model. Issue 4 (14th December 2020) - Rudland, Joy; Tweed, Mike; Jaye, Chrystal; Wilkinson, Tim J.
Abstract: Introduction: Learner neglect is a relatively new concept in education, and no suitable framework for its exploration has been devised. The aim of this study was to determine whether an existing framework, Glaser's framework of child neglect, could be applied to learner neglect in clinical learning environments. This was a retrospective analysis of data obtained as part of a related study. Method: Six focus groups were conducted with medical students in their early clinical years to explore their views of what experiences in medical education were challenging and why they presented a challenge. The transcript data were analysed using inductive content analysis, within an interpretivist approach in the development of categories. The identified categories were cross referenced with Glaser's framework categories replacing the carer with the teacher and the child with the learner. Results: Glaser's classifications of teacher (parent) behaviours were all identified in the negative aspects of medical learner clinical education including emotional unavailability/unresponsiveness, acting in a hostile manner, inappropriate inconsistent developmental interaction, failure to recognise individuality and failure to promote social adaption. Physical unavailability was identified as an additional category and is included in our proposed framework of learner neglect. Discussion: Adapting Glaser's framework was useful in considering learner neglect. Medical schools have a role in ensuring learning experiences are positive across contexts and to make explicit to teachers any behaviours that may appear as learner neglect. Applying this framework has the potential to make more explicit any subtle undermining teacher behaviours. Once explicit, there is a greater likelihood that behaviours may be reappraised both by the teacher and learner and modified to promote a more effective clinical learning experience. Abstract : Rudland et al. explore learner neglect in medical education and report various parallels to an existing framework of child neglect.